Determinant of Employee Performance in Banking Industry - I Gusti Ngurah Agung Yudisthi Surya Dananjaya; I Gusti Ayu Sugiati; Ni Wayan Sitiari (Journal of Tourism Economics and Policy, 2026)
This study investigated how employee engagement and organizational culture impact employee performance through organizational commitment. The study took place in Tabanan Regency and included workers from ten credit unions. The study included 338 BPR employees in its population. A sample size of 183 employees was established using the proportional sampling method. Validity and reliability tests were conducted on 30 participants not representative of the population for instrument evaluation. SEM-PLS was utilized to conduct hypothesis testing. The analysis findings demonstrate that employee engagement has a positive but insignificant impact on employee performance. Involvement in work positively impacts organizational commitment in a significant way. The impact of organizational culture on employee performance and commitment is positive and substantial. Employee performance is positively and significantly impacted by organizational commitment. The findings from the mediation analysis demonstrate that organizational commitment plays a mediating role in the relationship between work involvement, organizational culture, and employee performance.